Effect of crop management intensity on energy and carbon dioxide balance of two bioenergy Sorghum bicolor hybrids - Cabrera-Ariza, Antonio M.; Tozzini, Cristiano; Espinoza-Meza, Sergio E.; Santelices-Moya, Rómulo E.; Magni-Díaz, Carlos R.; Alonso-Valdés, Máximo F. (Italian Journal of Agronomy, 2018)
Although bioenergy sorghum has many traits that make it ideal for biofuel production, management conditions that can affect the productivity and sustainability of these systems are still poorly understood. This paper estimated the energy and CO2 balance of two bioenergy sorghum (Sorghum bicolor L. Moench.) hybrids (H128 and H133) cultivated during two growing seasons and under two different levels of crop management, high and low input. At the end of both growing season, sorghum was harvested for biomass yield determination. Calorific value and net energy production were also estimated. Crop management had important effects on sorghum CO2 and energy balance. The energy produced varied between 126 and 365 GJ ha–1 depending on crop management, hybrid and growing season. Regarding of the CO2 balance, the high level of crop management had a superior CO2 emission. However, the energy produced per kg of CO2 emitted was higher (>300%) than the energy produced with the use of fossil fuels. The use of bioenergy sorghum can contribute to better energy sustainability and reduced CO2 emission in Mediterranean ecosystems.